(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
The peculiarity of the method of pedagogical technology is that it projects the learning process, which ensures the achievement of the planned goals of education. Goalsetting, reviewing current results, breaking down learning material into individual pieces - these are the hallmarks of the learning process - are the hallmarks of a repetitive learning cycle.